2017
DOI: 10.1371/journal.pone.0187280
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative body weight change is associated with in-hospital mortality in cardiac surgical patients with postoperative acute kidney injury

Abstract: BackgroundPostoperative acute kidney injury (AKI) is common following cardiac surgery (CS). Body weight (BW) may be an amenable variable by representing the summation of the nutritional and the fluid status. However, the predictive role of perioperative BW changes in CS patients with severe postoperative AKI is never explored. This study aimed to evaluate this association.MethodsThis study was conducted using a prospectively collected multicenter cohort, NSARF (National Taiwan University Hospital Study Group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(54 reference statements)
1
4
0
Order By: Relevance
“…The sensitivity and specificity values for the NRS-2002 were 0•8 (0•76-0•84) and 0•89 (0•84-0•92), respectively, thus successfully identifying risk. Our results showed that both the NRS-2002 and AKI had a dose-response relationship between their severity and the adverse effect on the short-and long-term survival of the patients, which is consistent with previous studies (40,44,45) . Our finding suggests that both NRS-2002 scores ≥ 3 and AKI can worsen the short-and long-term prognosis of patients and the prognosis of the malnourished patient who develops AKI is far worse than that of the patient with normal nutritional status; thus, good nutritional support has been advocated in AKI.…”
Section: Discussionsupporting
confidence: 93%
“…The sensitivity and specificity values for the NRS-2002 were 0•8 (0•76-0•84) and 0•89 (0•84-0•92), respectively, thus successfully identifying risk. Our results showed that both the NRS-2002 and AKI had a dose-response relationship between their severity and the adverse effect on the short-and long-term survival of the patients, which is consistent with previous studies (40,44,45) . Our finding suggests that both NRS-2002 scores ≥ 3 and AKI can worsen the short-and long-term prognosis of patients and the prognosis of the malnourished patient who develops AKI is far worse than that of the patient with normal nutritional status; thus, good nutritional support has been advocated in AKI.…”
Section: Discussionsupporting
confidence: 93%
“…It has been reported that hyperlactatemia is an independent mortality predictor in patients with SA-AKI in the emergency department [ 50 ], postoperative AKI requiring RRT[29] and SA-AKI requiring CRRT [ 9 ]. However, other studies have shown that the initial lactate level is not independently associated with death in patients with SA-AKI requiring CRRT [ 10 , 51 ] or post-cardiovascular surgery AKI [ 32 ]. Moreover, in the literature, serum lactate has never been reported as an independent predictor of kidney recovery after AKI [ 6 , 29 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Renal injury is a common yet potentially serious complication after cardiac surgery and its pathophysiology is complex and multifactorial, which includes several factors such as exogenous and endogenous toxins, metabolic factors, ischemia-reperfusion injury, neurohormonal activation, embolization, hemodynamic alterations, along with in ammation and oxidative stress [11]. On the one hand, due to worse cardiac function or hypotension during the reoperation, the kidneys may suffer from ischemic damage.…”
Section: Discussionmentioning
confidence: 99%